Switzerland : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1997)
This Selected Issues paper and Statistical Appendix assesses Switzerland's recent real GDP performance in terms of underlying movements in potential output and the cyclical output gap. The paper highlights that Swiss real GDP has been stagnant since 1990, after expanding at an average rate of some 1 3/4 percent during 1977-90. The evidence presented indicates that potential output growth during 1991-95 was significantly below historical average. This paper also tries to assess the possible effects of stage 3 of European Monetary Union on Switzerland.